Sharp Hardy’s inequalities in Hilbert spaces - Dimitrov, Dimitar K. [UNESP]; Gadjev, Ivan; Ismail, Mourad E.H. (European Mathematical Society - EMS - Publishing House, 2024)
We study the behavior of the smallest possible constants d.a; b/ and dn in Hardy’s inequalities (Formula Presented) and (Formula Presented) The exact constant d.a; b/ and the precise rate of convergence of dn are established and the extremal function and the “almost extremal” sequence are found.
Keywords: almost extremal sequence; exact constant; extremal function; Hardy’s inequality